A PROPOSED ADVERTISING CAMPAIGN FOR GO NUTS DONUTS (March 2007) - Cruz, Kristel Ann P.; Espiritu, Minelle N.; Recto, Angelica Anne B. and Villanueva, Rochelle Jinna A. 4 0 16; 5 (2007)
u
Thesis (Undergraduate) Pamantasan ng Lungsod ng Maynila, 2007.;Bachelor of Science in Mass Communication.
Keywords: 2 -- 0; 6; 20; 20; 2